PENGARUH PROFITABILITAS, LIKUIDITAS DAN FAKTOR LAINNYA TERHADAP FRAUDULENT FINANCIAL STATEMENT - VINCENTSIUS ADITHYA SALIM; Rudi Riady (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The motive of this research of fraudulent financial statement is to acquire empirical evidence about the effect of profitability, liquidity, activity, leverage, assets composition, firm size, personal financial needs and ineffective monitoring on fraudulent financial statement. The research object used in this research is non-financial firms listed in Indonesian Stock Exchange from 2017 to 2020. Purposive sampling method is used as sampling selection in this research, so it requires criteria for taking samples to be examined. In the end, this research examined 81 companies that passed the criteria with a total of 324 data. Logistic regression is used in this research for hypothesis testing. The results of hypothesis testing confirmed that profitability, liquidity, activity, leverage, assets composition, firm size, personal financial needs and ineffective monitoring do not show any effect on fraudulent financial statement.